2012
DOI: 10.1029/2011gl050578
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the upper‐level warm core in the rapid intensification of a tropical cyclone

Abstract: [1] In this study, the rapid intensification (RI) of tropical cyclone is examined using a 72-h cloud-permitting prediction of Hurricane Wilma (2005) with a record-breaking intensity of 882 hPa. Results show the formation of an upper-level warm core from the descending air of stratospheric origin in the eye, which coincides with the onset of RI; it reaches the peak amplitude of more than 18°C from its initial conditions at the time of peak intensity. The descending air is associated with the detrainment of conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 64 publications
4
96
1
Order By: Relevance
“…The 900-m resolution in the central domain is used to better capture small-scale features associated with DWC formation and better resolve the DWC structural features. As shown in previous studies (e.g., [11,14,19,27]), DWCs appear in the TC eye with a typical radius of 10-20 km, so high-resolution simulations are necessary to capture the detailed formation of the DWC structure in the vortex core.…”
Section: Model Configurationmentioning
confidence: 94%
See 1 more Smart Citation
“…The 900-m resolution in the central domain is used to better capture small-scale features associated with DWC formation and better resolve the DWC structural features. As shown in previous studies (e.g., [11,14,19,27]), DWCs appear in the TC eye with a typical radius of 10-20 km, so high-resolution simulations are necessary to capture the detailed formation of the DWC structure in the vortex core.…”
Section: Model Configurationmentioning
confidence: 94%
“…As discussed in [11], an upper-level inflow may emerge if there exits a sufficiently strong inward pressure gradient in the 100-70 hPa layer. Two possible mechanisms for the development of such an inward pressure gradient are radiative cooling at the cloud top in the outer-core region, and the returning inflow associated with overshooting convective rings in the eyewall region as disccused in [19].…”
Section: Control Simulationsmentioning
confidence: 99%
“…3.2c) from the SI to RI initial category, but moderately deep and very deep precipitation do not increase until the later stage of RI (i.e., the RI continuing category; Figs Table 3.4. (2005) by Zhang and Chen (2012) showed that convective bursts occurred mostly in the upshear quadrant when the storm underwent RI. The largest area of > 1% occurrence of very deep precipitation is observed in SI storms (Fig.…”
Section: Trmm Pr Overpasses Selectionmentioning
confidence: 99%
“…1). Shearinduced ventilation can weaken a TC through three concomitant processes: (i) a dilution of the upper-level warm core by outward fluxes of high u e and PV values, which causes the central pressure to rise through hydrostatic arguments (Frank and Ritchie 2001;Zhang and Chen 2012); (ii) convective downdrafts that flush low-entropy air into the boundary layer (Riemer et al 2010(Riemer et al , 2013; and (iii) shear-induced updrafts outside the eyewall that transport high-entropy air from the boundary layer, further weakening the midlevel radial gradient of moist entropy across the eyewall (Gu et al 2015). The importance of shear height on TC intensification is examined (Tang and Emanuel 2012;Shu et al 2013;Wang et al 2015) to possibly develop new metrics from the total vertical wind profile (Fig.…”
Section: Introductionmentioning
confidence: 99%